'Bad' piped water and other perceptual drivers of bottled water consumption in Indonesia. (26th May 2017) - Prasetiawan, Teddy; Nastiti, Anindrya; Muntalif, Barti Setiani
Abstract : In countries that have established and have been maintaining a robust piped water system, bottled water has been perceived to be of better quality than piped water. We argue that piped water and bottled water cannot be easily compared in the Indonesian context. Drinking from tap water has never been accepted as the norm as piped water has no guarantee of purity and safety. The substantial marketing efforts of the bottled water industry highlight the appeal of bottled water in regard to, not only good water quality and physical health, but also taste, convenience, mental health, and social and environmental values. Despite many negative social and environmental issues associated with bottled water, this enigmatic commodity is becoming 'the' drinking water in Indonesia and is inseparable from modern life. WIREs Water 2017, 4:e1219. doi: 10.1002/wat2.1219 This article is categorized under: Engineering Water > Sustainable Engineering of Water Human Water > Water as Imagined and Represented Abstract : Bottled water is becoming 'the' drinking water in Indonesia and is inseparable from modern life. The appeal of bottled water is not only about good water quality and physical health, but also taste, convenience, mental health, and social and environmental values.